Acceptability, continuation and complication rate of postpartum insertion of intrauterine contraceptive device among Pakistani women - Ahsan, Azra; Ali, Aleya (Journal of the Pakistan Medical Association, 2023)
Objective: To determine level of acceptability, continuation and complication rate associated with postpartum intrauterine contraceptive device uptake. Methods: The multicentre study was conducted from April 2012 to December 2020 in selected health facilities across Pakistan. After approval from the ethics review committee of the Pakistan Medical Association data was analysed retrospectively. This comprised women attending antenatal clinics and those who came in labour without prior registration. The subjects were counselled, and those who consented were given family planning services of their choice, particularly postpartum intrauterine contraceptive device. The subjects were followed up at 6 weeks and then again at 6 months. Data was analysed using SPSS 20.0. Results: Of the 3,523,404 women available, 525,819(15%) were counselled. Of them, 208,663(39.7%) were aged 25-29 years, 185,495(35.3%) had secondary education, 476,992(90.7%) were unemployed, and 261,590(49.74%) had 1-2 children. Of the total, 387,500(73.7%) consented to receive postpartum intrauterine contraceptive device, 149,833(38.7%) actually came for insertion. Those who did receive postpartum intrauterine contraceptive device were 146,318(97.65%), and, of them, 58,660(40%) were lost to follow-up. Acceptance and uptake of postpartum intrauterine contraceptive device was positively and significantly dependent on the professional level of counsellor and the place of counselling (p<0.01). Age, education, number of living children and gravida were significantly associated with device insertion status (p<0.01). Of the 87,658(60%) subjects followed up, those who came at 6 weeks were 30,727(35.05%) and device discontinuation rate was 3,409(11.09%). At 6 months, there were 56,931(64.94%) follow-ups and the discontinuation rate was 6,395(11.23%). Conclusion: Counselling done by doctors in early labour positively influenced the postpartum intrauterine contraceptive device insertion rate. Key Words: Counselling, Acceptability, Insertion, Non-insertion reasons, Postpartum intrauterine contraceptive device, PPIUCD.